Produksi Bioetanol Dari Pati Sorgum Dengan Variasi Penambahan Tween 80 Dan Ekstrak Cordyceps Sinesis Mycelum - Novebriantika Novebriantika; Elvi Yenie; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The high dependence on fossil fuels and eco friendly fuel needs cause development of biofuels. Bioethanol is one of the biofuels that lately developed. In this research, theproduction of bioethanol from sorghum starch with the addition of Tween 80 and extract of Cordyceps sinensis mycelium variation as a supplement. The purpose of this study was todetermine the effect of variations in the addition of Tween 80 and extract of Cordyceps sinensis mycelium for the bioethanol yield and determine the effect of variations in thefermentation process time for the bioethanol yield. Sorghum starch was hydrolyzed to produce glucose using alpha amylase and glucoamylase enzyme. After hydrolysis wascomplete, the fermentation process was carried out in a 2L fermenter with variation time of 24, 48, 72, and 96 hours, variations addition of Tween 80: extract of Cordyceps sinensismycelium were 15 ml: 1.5 g; and 20 ml: 2.0 g. Bioethanol concentration was analyzed by gas chromatography. The addition of tween 80 and extract of Cordyceps sinensis mycelium effect on the activity of Saccharomyces cerevisiae in converting the sorghum starch into bioethanol, which can preserve viability of cell until the end of fermentation and produced higher ethanol yield. The production of bioethanol from sorghum starch results the best conditions on addition 20 ml of tween 80 and 2.0 grams of extract of Cordyceps sinensis mycelium in 96 hours fermentation time with concentration of bioethanol is 9,15024 mg/ml.Keywords: bioethanol, Cordyceps sinensis mycelium, hydrolysis, sorghum starch, tween 80